The functional development of the rumen is influenced by weaning and associated with ruminal microbiota in lambs. Issue 4 (1st August 2022) - Li, Chong; Zhang, Qian; Wang, Guoxiu; Niu, Xiaolin; Wang, Weimin; Li, Fei; Li, Fadi; Zhang, Zhaocai
Abstract: Rumen development is critical for the development of early lambs. This work aims to evaluate the effects of abrupt weaning at day 21 on rumen fermentation, histomorphological traits and the ruminal microbiota compared with continuous suckling. Twelve pairs of artificially reared full-sib neonatal male Hu lambs were allocated to two groups, one of which was weaned at day 21 (EW group) and the other which was not weaned (CON group). At day 26 and day 49, six lambs from each group were randomly selected and sacrificed to collect ruminal contents and rumen tissue samples. Results showed that weaning influenced the fermentation parameters in the rumen, and altered the microbial community composition on day 49 ( p < 0.05). Several genera were associated with rumen fermentation parameters ( p < 0.05). Volatile fatty acid (VFA) concentration is the key parameter impacting microbiota composition. Weaning influenced the expression of genes associated with VFA metabolism and regulation of cell proliferation ( p < 0.05). In conclusion, weaning significantly influenced the morphological and functional development of the rumen, and bacterial community composition. The microbial community composition was strongly associated with rumen weight and fermentation profiles, but not with morphological development.